Influence Of Metamemory Maturity On Arabic Vocabulary Size Achievement Of Pre-University Student In Selangor/ تأثير نضج ما وراء الذاكراة على تحصيل حجم المفردات العربية لدى طلبة ما قبل الجامعة في سلانجور - Jali, Khairul Anuar; Baharudin, Harun (Ijaz Arabi Journal of Arabic Learning, 2024)
The research investigates the relationship between metamemory maturity and achievement of Arabic vocabulary size among STAM students in Selangor. The research sample consisted of 185 male and female students of Sijil Tinggi Agama Malaysia (STAM) in different government-assisted religious schools (SABK) in Selangor. This study uses a survey design of 271 students in Selangor. A total of 185 students were selected as respondents through the proportional strata sampling technique. The study utilized a survey design and employed descriptive and inferential analyses. Two instruments were used: a questionnaire on metamemory maturity and a test on knowledge of Arabic vocabulary size. Findings revealed a medium level of metamemory maturity (mean score: 3.79) and Arabic vocabulary size achievement (mean score: 77.7). A significant correlation (r = 0.18) was found between metamemory maturity and vocabulary size achievement. Regression analysis indicated that metamemory maturity contributes significantly (β=0.184, t=2.538, p=0.012), explaining 3.4% of the variance in Arabic vocabulary size mastery. The study suggests that metamemory maturity influences students' Arabic vocabulary size mastery.